Tracking Neural Progenitor Cell Migration in the Rodent Brain Using Magnetic Resonance Imaging - Mallett, Christiane L.; Shuboni-Mulligan, Dorela D.; Shapiro, Erik M. (Frontiers in Neuroscience, 2019)
The study of neurogenesis and neural progenitor cells (NPCs) is important across the biomedical spectrum, from learning about normal brain development and studying disease to engineering new strategies in regenerative medicine. In adult mammals, NPCs proliferate in two main areas of the brain, the subventricular zone and the subgranular zone, and continue to migrate even after neurogenesis has ceased within the rest of the brain. In healthy animals, NPCs migrate along the rostral migratory stream (RMS) from the subventricular zone to the olfactory bulb, and in diseased animals, NPCs migrate towards lesions such as stroke and tumors. Here we review how MRI-based cell tracking using iron oxide particles can be used to monitor and quantify NPC migration in the intact rodent brain, in a serial and relatively non-invasive fashion. NPCs can either be labeled directly in situ by injecting particles into the lateral ventricle or RMS, where NPCs can take up particles, or cells can be harvested and labeled in vitro, then injected into the brain. For in situ labeling experiments, the particle type, injection site, and image analysis methods have been optimized and cell migration toward stroke and multiple sclerosis lesions has been investigated. Delivery of labeled exogenous NPCs has allowed imaging of cell migration towards more sites of neuropathology, which may enable new diagnostic and therapeutic opportunities for as-of-yet untreatable neurological diseases.